Caring for the elderly in Japan and the US : practices and policies - Long, Susan Orpett (Routledge advances in Asia-Pacific studies., 2000)
This volume provides a broader picture of how elder care is defined at a time when ageing is becoming increasingly defined as a social problem. It is a valuable source for researchers in health and welfare, social policy and gerontology.